Śaratcandra kī śreshṭha kahāniyāṃ - Caṭṭopādhyāẏa, Śaratcandra 1876-1938 (Śāśvata Priṇṭarsa eṇḍa Pabliśarsa, 2012)
Selected stories of a Bengali author
In Devanagari-Schr., Hindi. - Short stories. - Translated from Bengali
Keywords: Caṭṭopādhyāya, Śaratcandra / 1876-1938 / Translations into Hindi